School Excellence and Acceleration Policy: A Review of Theory and Implementation - Niswatin, Niswatin; Damayanti, Erika Selphie; Jonathan, Bouyea; Joshua, Wang (Lingeduca: Journal of Language and Education Studies, 2023)
This research aims to describe the advantages, disadvantages, and ideal picture of superior schools and acceleration programs. The research method used is descriptive qualitative with literature study. The results of the theoretical review present concepts and definitions of excellent schools and acceleration programs. The advantages of excellent schools include a quality learning environment, skilled teachers, and a curriculum focused on critical skills. Disadvantages of excellent schools include high competition and lack of involvement in non-academic aspects. The strengths of accelerated programs are that the academic challenges match the abilities of gifted and bright students. Disadvantages of accelerated programs include social and emotional gaps and a lack of focus on non-academic skills. The ideal picture of excellent schools and accelerated programs includes a balanced approach between academic and non-academic needs, emotional and social support for students, and flexibility in the curriculum. In conjunction with the curriculum reform in Curriculum 2013 (K13), a school policy with an SKS (Satuan Kredit Semester) system was created that emphasizes students' independent and collaborative learning abilities based on Independent Learning Activity Units (UKBM).